Facilitating co-production in public services: Empirical evidence from a co-design experience with family caregivers living in a remote and rural area. (February 2021) - Gheduzzi, Eleonora; Morelli, Niccolò; Graffigna, Guendalina; Masella, Cristina
The involvement of vulnerable actors in co-production activities is a debated topic in the current public service literature. While vulnerable actors should have the same opportunities to be involved as other actors, they may not have the needed competences, skills and attitudes to contribute to this process. This paper is part of a broader project on family caregivers' engagement in remote and rural areas. In particular, it investigates how to facilitate co-production by looking at four co-design workshops with family caregivers, representatives of a local home care agency and researchers. The transcripts of the workshops were coded using NVivo, and the data were analysed based on the existing theory about co-production. Two main findings were identified from the analysis. First, the adoption of co-production by vulnerable actors may occur in conjunction with other forms of engagement. Second, the interactions among facilitators and providers play a crucial role in encouraging the adoption of co-production. We identified at least two strategies that may help facilitators and providers achieve that goal. However, there is a need for an in-depth understanding of how facilitators and providers should interact to enhance implementation of co-production.